2019
DOI: 10.31234/osf.io/btcxm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facial Appearance and Electoral Success of Male Italian Politicians: Are Trustworthy-Looking Candidates More Successful In Corrupt Regions?

Abstract: People rely on the facial appearance of political candidates when voting. Here, we examine whether perceptions of competence, trustworthiness, or attractiveness are associated with electoral success in the 2016 Italian local elections. In line with situational leadership theory, we also test whether trait preferences for politicians vary as a function of election context. Specifically, we examine if trustworthy-looking politicians are more successful in regions where political corruption is a salient issue. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Indeed, attractive politicians are perceived to be better and more proficient representatives, they can conquer more attention in the mainstream media as their decent appearance offers them an election gain. While a study by Jaeger, Evans and Van Beest (2021) reveals that attractive-looking candidates are more victorious in elections, to the contrary, a study by Wigginton and Stockemer (2021) found that physical attraction does not contribute in influencing the vote share of a candidate. As such the perception is that good looking candidates, are capable of being more successful in raising funds as well as getting more confirmations, which leads to their triumphing in the polls.…”
Section: Towards a Conceptual Perspective Of Electionsmentioning
confidence: 94%
“…Indeed, attractive politicians are perceived to be better and more proficient representatives, they can conquer more attention in the mainstream media as their decent appearance offers them an election gain. While a study by Jaeger, Evans and Van Beest (2021) reveals that attractive-looking candidates are more victorious in elections, to the contrary, a study by Wigginton and Stockemer (2021) found that physical attraction does not contribute in influencing the vote share of a candidate. As such the perception is that good looking candidates, are capable of being more successful in raising funds as well as getting more confirmations, which leads to their triumphing in the polls.…”
Section: Towards a Conceptual Perspective Of Electionsmentioning
confidence: 94%
“…In everyday life, people are embedded in various contexts when forming impressions of others. A perceiver's context can encompass one's broader culture (Jaeger et al, 2019), personal environment (Barrett & Kensinger, 2010), or experienced situation (Rauthmann & Sherman, 2018). Although research on the influence of perceiver contextual factors on impression formation is scarce, a recent twin study found that genes explain little variability in facial impressions compared to one's personal environment (Sutherland et al, 2020), encompassing local factors related to one's upbringing and community.…”
Section: Do Perceiver Contexts Influence Impression Formation?mentioning
confidence: 99%
“…This affective contagion process is most likely to happen for positive emotional expressions while also highly dependent on the political context (Sullivan and Masters, 1988;Homan et al, 2022). In addition, smiling may unconsciously produce a halo effect, increasing perceptions of attractiveness, competence and trustworthiness (Montepare and Dobish, 2003;Oosterhof and Todorov, 2008;Todorov et al, 2008;Zebrowitz, 2017).These perceptions have been found to predict election outcomes (Todorov et al, 2005;Laustsen and Petersen, 2016a;Little et al, 2012;Jaeger et al, 2019;Mattes and Milazzo, 2014). Second, people deduce important social information from leaders' emotional expressions, such as their goals and intentions (Van Kleef, 2009, 2010Hareli and Hess, 2010).…”
Section: Introductionmentioning
confidence: 99%